2011
DOI: 10.1111/j.1755-3768.2010.02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of intravitreal bevacizumab (Avastin®) on retrobulbar hemodynamics in patients with neovascular age-related macular degeneration

Abstract: ABSTRACT.Purpose: To evaluate the short-term effects of intravitreal bevacizumab on retrobulbar hemodynamics in patients with neovascular age-related macular degeneration (AMD). Methods: This study was carried out at Ataturk Training and Research Hospital 1st Ophthalmology Clinic, Ankara. Fourteen patients with neovascular AMD, who were treated with intravitreal injection of bevacizumab, were included in this study. Peak systolic velocity (PSV), end-diastolic velocity (EDV) and resistivity index (RI) were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…The results of the study revealed that PSV-OA, MV-OA and PSV-MCA showed significant decreases after IVB treatment. Our findings were compatible with previous reports which demonstrated decreased OBF velocities after IVB treatment in miscellaneous ophthalmic diseases [13,14,19]. …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results of the study revealed that PSV-OA, MV-OA and PSV-MCA showed significant decreases after IVB treatment. Our findings were compatible with previous reports which demonstrated decreased OBF velocities after IVB treatment in miscellaneous ophthalmic diseases [13,14,19]. …”
Section: Discussionsupporting
confidence: 83%
“…Besides, it has been shown that decreased blood flow velocities accompany the increased RI [13]. Studies have proposed that a decrease in blood flow velocities with increased RI is related to the thromboembolic side effect of bevacizumab in the arterial system [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of a major increase of RBFV occurring in arterioles supports the theory of vasoconstriction being the major driver of increase in RBFV. 20,21 In this set of patients, we found only a weak association between changes in IOP and blood flow velocity (data not shown). We therefore conclude that changes in RBFV were not substantially affected by changes in IOP.…”
Section: Main Findingsmentioning
confidence: 90%
“…[54][55][56][57][58] After treatment with intravitreal anti-VEGF (bevacizumab), an initial decrease of the blood flow velocity in the central retinal 56 and short posterior ciliary arteries 56,57 had been detected in the early post-operative period, but returned to pre-operative values after one month. 56 On the other hand, combination therapy of exudative ARMD with intravitreal triamcinolone and photodynamic therapy had no significant effect on the retrobulbar blood flow parameters. 58 Photodynamic therapy alone had a temporary effect on the circulatory parameters in the short posterior ciliary artery that returned to the pre-treatment values four weeks later.…”
Section: -53mentioning
confidence: 99%